-repetition-rate femtosecond Raman laser. (July 2016) - Didenko, N.V.; Konyashchenko, A.V.; Kostryukov, P.V.; Losev, L.L.; Pazyuk, V.S.; Tenyakov, S.Yu.
Abstract: A femtosecond Raman laser utilising compressed hydrogen is experimentally investigated under pumping by radiation from a -repetition-rate Ti : sapphire laser. In the regime of double-pulse pumping, the conditions are determined, which correspond to the minimal energy dispersion of Stokes pulses. The optical scheme is realised, which is capable of ensuring the long-term stability of the average power of the first Stokes component with a variation of less than 2 %. The Stokes pulses are produced with a pulse duration of and energy of at a conversion efficiency of 14 %.